2020
DOI: 10.47435/naskhi.v2i1.154
|View full text |Cite
|
Sign up to set email alerts
|

Facebook Sebagai Alternatif Media Pengembangan Maharah Kitabah

Abstract: Artikel ini bertujuan untuk mengungkapkan peran facebook sebagai media alternatif dalam pengembangan kemampuan Maharah Kitabah para pengguna. Penelitian ini menggunakan metode kualitatif deskriptif dengan mengungkapkan berbagaimacam fenomena yang terjadi khususnya pada aspek penggunaan media sosial facebook dalam menunjang pengembangan kemampuan Maharah Kitabah. Peneliti juga menggunakan pendekatan literatur dan pernyataan dari beberapa ahli untuk memperkuat hasil penelitian, Dalam penelitian ini, Peneliti men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…This study shows that using YouTube significantly improves listening skills for non-Arabic speaking students (Aboudahr, 2020;Jabbar et al, 2022). The results of this study are the same as AlSaleem's research; the results of this study recommend that social networking media (Facebook) can be utilized to improve speaking and listening skills (AlSaleem, 2018) and writing skills (Linur & Mubarak, 2020), this conclusion is also in line with Mahmud's research (Facebook and Instagram) with the results of the study that both online platforms can be used in English Language Teaching (Mahmud et al, 2022). Another study relevant to this research is Ubaidillah's research, which says that using online media can increase students' motivation in learning istima' 1 (Ubaidillah, 2020).…”
Section: Introductionsupporting
confidence: 78%
“…This study shows that using YouTube significantly improves listening skills for non-Arabic speaking students (Aboudahr, 2020;Jabbar et al, 2022). The results of this study are the same as AlSaleem's research; the results of this study recommend that social networking media (Facebook) can be utilized to improve speaking and listening skills (AlSaleem, 2018) and writing skills (Linur & Mubarak, 2020), this conclusion is also in line with Mahmud's research (Facebook and Instagram) with the results of the study that both online platforms can be used in English Language Teaching (Mahmud et al, 2022). Another study relevant to this research is Ubaidillah's research, which says that using online media can increase students' motivation in learning istima' 1 (Ubaidillah, 2020).…”
Section: Introductionsupporting
confidence: 78%
“…Language skills are not only in the aspects of istima, qira'ah, kitabah, but also the ability to speak (kalam) (Linur & Mubarak, 2020). Moreover, the kalam (speaking) aspect is a very visible marker of students' language skills (Syamaun, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…1, No. 1, January 2023, 25-34 Linur also revealed that the form of writing presented in social media positively impacts Arabic language skills, such as reading skills (Linur & Mubarak, 2020).…”
Section: Writingmentioning
confidence: 99%
“…Instagram social media is a concrete example of technological developments in modern times. In the context of Arabic language learning media, the use of Instagram as a medium for Arabic language learning has begun to attract much interest among educators (Audina & Muassomah, 2020;Saputra et al, 2021) besides other media such as YouTube (Hamidah & Marsiah, 2020;Marsiah et al, 2021), and Facebook (Linur & Mubarak, 2020). Based on the results of researchers' observations, on Instagram, there are many accounts containing Arabic language learning content.…”
Section: Introductionmentioning
confidence: 99%